2014
DOI: 10.1097/qai.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multiple Data Sources and Individual Case Investigation to Refine Surveillance-Based Estimates of the HIV Care Continuum

Abstract: Objectives To assess the HIV care continuum among HIV-infected persons residing in Seattle & King County, Washington at the end of 2011 and compare estimates of viral suppression derived from different population-based data sources. Methods We derived estimates for the HIV care continuum using a combination of HIV case and laboratory surveillance data supplemented with individual investigation of cases that appeared to be unlinked to or not retained in HIV care, a jurisdiction-wide population-based retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 19 publications
2
28
1
Order By: Relevance
“…Most existing literature on DTC has focused on the impact various linkage-to-care definitions have on the Care Continuum,7,8 or validating HIV surveillance–based estimates through field investigation, medical records, direct patient access, or other methodologies 913. Just a handful of studies have addressed the feasibility of using HIV surveillance data to identify, locate, and link out-of-care (OOC) individuals to HIV medical care.…”
Section: Data-to-care Initiativesmentioning
confidence: 99%
“…Most existing literature on DTC has focused on the impact various linkage-to-care definitions have on the Care Continuum,7,8 or validating HIV surveillance–based estimates through field investigation, medical records, direct patient access, or other methodologies 913. Just a handful of studies have addressed the feasibility of using HIV surveillance data to identify, locate, and link out-of-care (OOC) individuals to HIV medical care.…”
Section: Data-to-care Initiativesmentioning
confidence: 99%
“…The percentage of persons who link to HIV care within 3 months after HIV diagnosis is among the highest reported in the US (92% in 2011). 10 Nonetheless, many PLWHA in Washington are not consistently engaged in care and are not virologically suppressed. 10,11 We began a health department-based intervention to promote HIV care relinkage and ART use among PLWHA in King County, WA in 2011.…”
mentioning
confidence: 99%
“…10 Nonetheless, many PLWHA in Washington are not consistently engaged in care and are not virologically suppressed. 10,11 We began a health department-based intervention to promote HIV care relinkage and ART use among PLWHA in King County, WA in 2011. As part of this program, we systematically collected data from patients about their perceived barriers to HIV care and ART initiation and reasons for ART discontinuation, which we present in this article.…”
mentioning
confidence: 99%
“…Prior work in King County, Washington demonstrated that individual case investigations led to a large decrease in the number of persons estimated to be out of HIV care. 18-20 However, the generalizability of this finding to other areas has been unclear. Local and state health department staff from six Northwest US states (Alaska, Idaho, Montana, Oregon, Washington, and Wyoming) and investigators from University of Washington (UW) Center for AIDS Research (CFAR) conducted a coordinated effort to refine estimates of retention in care with individual case investigation.…”
Section: Introductionmentioning
confidence: 85%